2020
DOI: 10.1002/pri.1860
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy in children hospitalized with traumatic brain injury in a South African tertiary paediatric hospital

Abstract: Introduction: Physical impairments following traumatic brain injury (TBI) may limit participation in daily living. Physiotherapy could assist in managing these limitations, however, there is a paucity of literature on the physiotherapy management of children in the acute phase of TBI. Objectives: To describe the characteristics, course and outcome of children hospitalized with TBI, with specific reference to the role of physiotherapy. Methods: A retrospective folder review of all children (n = 130, median 5.37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, the first and only study in South Africa that evaluated the effects of early neurorehabilitation (Physiotherapy) in the management of paediatric traumatic brain injury and concluded that children who received early physiotherapy services (airway clearance: vibrations, tracheal stimulation, positioning, manual cough assist, suctioning; functional treatment: mobilization in and out of bed, strengthening, get education, bed mobility, caregiver education) well tolerated it and had better outcomes. Also, most of the children who received early neurorehabilitation during hospitalization were not recommended for further treatment after discharge [ 28 ]. They, however recommended further studies with larger sample to draw adequate conclusions on the role of early neurorehabilitation in TBI outcome.…”
Section: Rehabilitation and Its Importance In Overall Tbi Carementioning
confidence: 99%
“…However, the first and only study in South Africa that evaluated the effects of early neurorehabilitation (Physiotherapy) in the management of paediatric traumatic brain injury and concluded that children who received early physiotherapy services (airway clearance: vibrations, tracheal stimulation, positioning, manual cough assist, suctioning; functional treatment: mobilization in and out of bed, strengthening, get education, bed mobility, caregiver education) well tolerated it and had better outcomes. Also, most of the children who received early neurorehabilitation during hospitalization were not recommended for further treatment after discharge [ 28 ]. They, however recommended further studies with larger sample to draw adequate conclusions on the role of early neurorehabilitation in TBI outcome.…”
Section: Rehabilitation and Its Importance In Overall Tbi Carementioning
confidence: 99%